Study on innovation of breakfast packaging for student / Nur Amalina Khairudin - Khairudin, Nur Amalina (Faculty of Art and Design, 2015)
Food packaging has evolved from simply a container to hold food to something today that can play an active role in various aspects. As we all know, packaging today plays an important role in the quality of food products by providing protection from environmental. Food packaging itself can retard product deterioration, retain the beneficial effects of processing, extend shelf-life, and maintain or increase the quality and safety of food. Besides that, packaging is a communication device providing details about the product, including price, contents, Ingredients and nutritional value as well as cooking instructions and recommended use by dates (Ahmed, Ahmed & Salman 2005). Furthermore, a package is the face of a product and often' is the only product exposure consumers experience prior to purchase. Consequently, distinctive or innovative packaging can boost sales in a competitive environment. The package may be designed to enhance the product image and/or to differentiate the product from the competition. The package also can be design to make foods to be easier and faster to consume as we are living in a generation where time flew very fast. With that purpose, this current study focuses on an exploration in people's views on the product design that will very much benefit in a person's busy lifestyle. This study adopts questionnaire research method which 'is often seem a logical and easy option as a way of collecting information from people. In addition, large amounts of information can be collected from a large number of people in a short period of time and in a relatively cost effective way. The result of this study indicates that innovation in breakfast packaging should be done, because it make life more easier and help student to get the nutrition in early in the morning.